Nutrition as a missing piece in the development of youth male soccer players: A scoping review and future directions - Martinho, D.; Gonzalo-Skok, O.; Chamari, K.; Field, A.; Clemente, F.; Rebelo, A.; Gouveia, É.; Teixeira, V. H.; Zmijewski, P.; Mendes, P.; Campos, P.; Sarmento, H. (Biology of Sport, 2026)
The literature on nutrition in soccer has extensively focused on adult male and female soccer players, while knowledge regarding nutritional issues in youth soccer players remains limited. This review aims to summarize the findings related to nutritional habits and ergogenic aid practices among male youth soccer players. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) Checklist, four databases were consulted on September 17, 2024. Studies that included youth soccer players and examined daily energy intake or expenditure, as well as the effects of ergogenic aids on performance, met the eligibility criteria for this review. In total, 42 studies were considered. Among these, 22 studies focused on energy expenditure and dietary intake, while 20 studies investigated the effects of ergogenic aids on performance. Overall, a negative energy balance was observed; however, after adjusting for the underestimation of energy intake, an adequate intake compared to energy expenditure was found in this review. Additionally, carbohydrate intake tended to decrease with age, while protein intake remained stable throughout adolescence. The topic of macronutrient periodization in youth players requires further research, as no data is currently available regarding macronutrient intake. Additionally, data concerning the effects of ergogenic aids on performance is limited due to variability in methodological procedures. Nevertheless, caffeine and creatine appear to have a positive effect on physical capabilities. This review provides reference data for nutritionists working with youth soccer players and highlights the need for future research in this area.